Chemical composition and antioxidant activity of cereal bar source of dietary fiber and phenolic compounds (Research, Society and Development, 2023)
The objective of this work was to analyze the chemical composition and evaluate the antioxidant capacity, the concentration of bioactive compounds of a cereal bar added with whole cowpea flour (Vigna unguiculata (L.) Walp) and Apis mellifera bee honey. These regional raw materials were used in the development of the cereal bar in order to increase bioactive compounds and improve the nutritional quality of this product. Analysis of centesimal composition, caloric content, dietary fiber, bioactive compounds and antioxidant activity were carried out. The use of the BRS Tumucumaque cultivar promoted an increase in the nutritional value of the developed product. The food bar exhibited very high levels of dietary fiber, which makes it a food classified as high in dietary fiber. It showed expressive levels of total phenolics, total flavonoids, condensed tannins and antioxidant activity. The use of regional raw materials in the production of food bars proved to be a great option in the supply of nutrients and bioactive compounds.